Association of serum vitamin D with asthma and atopy in childhood: review of epidemiological observational studies - Kolokotroni, Ourania; Middleton, Nicos; Kouta, Christiana; Raftopoulos, Vasilios; Yiallouros, Panayiotis K. (My University, 2015)
During the last decades, vitamin D deficiency has re-emerged worldwide affecting not only population’s bone health, but also several other conditions including asthma and allergies. Increasing number of published epidemiological studies in the last seven years have examined the role of vitamin D deficiency in childhood in several outcomes including asthma diagnosis, asthma disease severity, allergic sensitization and atopy. This review presents evidence on this association from a systematic search in the literature of all available observational studies and their limitations. A total of 33 studies were identified: 3 prospective, 16 case-control and 14 cross-sectional studies. Overall, most of the case-control studies tend to report that asthmatics have lower vitamin D levels/status as compared to healthy children, although most of these studies are mainly descriptive in nature and tend to provide only crude, unadjusted comparisons. Studies that investigated the association of vitamin D with the prevalence, development and/or severity of asthma gave mixed findings, with the exception of studies that focused on vitamin D and severity of asthma which suggest a positive association of vitamin D levels with better asthma control, reduced use of asthma medication, fewer asthma exacerbations and lower utilisation of health care facilities for urgent treatment. Insufficient evidence also exists for the association of inadequate vitamin D status with higher risk of atopic sensitization. The lack of adequate number of prospective studies, the variable definitions for case ascertainment, the wide age range of the participants, and commonly the inadequate control for confounders make inferences difficult. Future studies are needed with a prospective design and repeated measurements of vitamin D to provide critical information on the timing and dosage of future vitamin D supplementation interventions.
Keywords: Asthma; Atopy; Children; Epidemiology; Review; Vitamin D.